2019
DOI: 10.1186/s13104-019-4511-x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective investigation of IgM antibodies against Zika virus in serum from febrile patients in Mozambique, 2009–2015

Abstract: Objective Zika virus (ZIKV) has emerged as an important health problem worldwide. The aim of this study was to investigate the occurrence, geographical distribution and trend of immunoglobulin M (IgM) antibodies against ZIKV between 2009 and 2015 in Mozambique. Results The median age of participants was 3 years [interquartile range (IQR): 1.0–6.0 years)] and 56.5% (480/850) of them were male. Of the 850 samples, 42 (4.9%) were positive for IgM antibodies against ZIKV. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
1
2
Order By: Relevance
“…Data on ZIKV epidemiology are scarce in the country. This study reported a frequency of IgM anti-ZIKV of 9.2%, which is higher than the prevalence of 4.9% found in a recent retrospective study conducted among febrile children aged 1 to 15 years old in Mozambique (20), suggesting that the frequency of ZIKV is increasing in the country. Similar to CHIKV, we believe that several factors are behind the potential increase in the frequency of ZIKV, such as human behaviors and climate and environmental changes (21-23) (24).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Data on ZIKV epidemiology are scarce in the country. This study reported a frequency of IgM anti-ZIKV of 9.2%, which is higher than the prevalence of 4.9% found in a recent retrospective study conducted among febrile children aged 1 to 15 years old in Mozambique (20), suggesting that the frequency of ZIKV is increasing in the country. Similar to CHIKV, we believe that several factors are behind the potential increase in the frequency of ZIKV, such as human behaviors and climate and environmental changes (21-23) (24).…”
Section: Discussioncontrasting
confidence: 78%
“…The higher frequency of IgM antibodies against CHIKV and ZIKV among malaria positive cases as compared to that found among febrile patients is a matter for further investigation but might suggest an overlap in the circulation of malaria, CHIKV and ZIKV in Mozambique. This study found a higher frequency of co-occurrence of IgM anti-CHIKV and malaria as compared to previous studies conducted in the country (13, 20), as well as in other countries in the continent (31-33).…”
Section: Discussioncontrasting
confidence: 57%
“…Although the real burden of arboviral and zoonotic diseases is unknown in the country due to the lack of a surveillance system for these diseases, dengue has been recognized as an emerging public health problem, especially in the city of Pemba, Cabo Delgado province, where it caused two outbreaks, the most recent in 2014 (6,7). Conversely, although outbreaks of Chikungunya, Zika, and Leptospirosis have not been clearly detected, serological studies have pointed to their endemic transmission across the country (8)(9)(10)(11)(12)(13). Furthermore, Aedes mosquitoes (Ae.…”
Section: Introductionmentioning
confidence: 99%